Revitalisasi Budaya Pajak di Kampus: Gerakan Pojok Pajak sebagai Sarana Edukasi dan Pendampingan SPT Tahunan - Sudrajat, Enjat; Permatasari, Novelia Kiki; Dasmaran, Verliani; Rachman, Nono Arief; Sutihat, Eva; Rifa’i S, Bachtiar; Mi’rajiah, Neng Septiani Fadilatul; Yulianti, Masyayu; Ramadhani, Muhamad; Deliyanti, Deliyanti (Jurnal Pustaka Dianmas, 2025)
Compliance in reporting Annual Tax Returns (SPT) is one form of citizen contribution in supporting state revenue through taxes. Unfortunately, the level of tax literacy and awareness among the academic community, especially students and education staff, is still relatively low. This community service activity aims to build a culture of tax compliance on campus through the implementation of the Tax Corner Movement as a means of education and assistance in reporting Annual Tax Returns. The implementation method includes socialization, technical training on filling out SPTs using e-Filing, and direct assistance services through the Tax Corner booth on the Mathla'ul Anwar University Campus. The results of the activity showed an increase in participants' understanding of independent tax reporting procedures. As many as 85% of participants felt helped by the existence of this service, and 72% of them successfully completed their SPT reports on time. This activity proves that a collaborative and educational approach on campus can encourage increased tax compliance, especially for first-time taxpayers. The Tax Corner Movement is worthy of replication as a model of sustainable community service in building a tax culture from an early age.